Current MR-Enterography in the Diagnosis of Crohn’s Disease, an Update. - Hasan, Aydın (Journal of Cancer Genetics And Biomarkers, 2014)
Objective: To utilize the effectiveness of MR-Enterography as a potential investigating marker for the diagnosis of Crohn’s disease. Conclusion: This article reviews the technique of performing MR enterography which aids in the diagnosis of Crohn’s disease, it also serves accurate information about the severity of the disease and complications of it that may guide for the surgical or medical treatment.
Keywords: MR-Enterography-Crohn-imaging-bowel